Participatory training scheme in area-based development strategy. - Occidental, Alicia P. ([College, Laguna] University of the Philippines at Los Baños, 1989)
Summary of a Ph.D. Dissertation in Community Development... presented in the RREM seminar series... June 18, 1988 at the Agricultural Education Lecture Hall, DAERS, UP at Los Baños.
Keywords: Rural development -- Citizen participation; Community development -- Citizen participation